Extending the plasmonic lifetime of tip-enhanced Raman spectroscopy probes. Issue 19 (3rd May 2016) - Kumar, Naresh; Spencer, Steve J.; Imbraguglio, Dario; Rossi, Andrea M.; Wain, Andrew J.; Weckhuysen, Bert M.; Roy, Debdulal
Abstract : Relationship between plasmonic lifetime of tip-enhanced Raman spectroscopy probes and environments with different oxygen and moisture content is investigated systematically. Abstract : Tip-enhanced Raman spectroscopy (TERS) is an emerging technique for simultaneous mapping of chemical composition and topography of a surface at the nanoscale. However, rapid degradation of TERS probes, especially those coated with silver, is a major bottleneck to the widespread uptake of this technique and severely prohibits the success of many TERS experiments. In this work, we carry out a systematic time-series study of the plasmonic degradation of Ag-coated TERS probes under different environmental conditions and demonstrate that a low oxygen (<1 ppm) and a low moisture (<1 ppm) environment can significantly improve the plasmonic lifetime of TERS probes from a few hours to a few months. Furthermore, using X-ray photoelectron spectroscopy (XPS) measurements on Ag nanoparticles we show that the rapid plasmonic degradation of Ag-coated TERS probes can be correlated to surface oxide formation. Finally, we present practical guidelines for the effective use and storage of TERS probes to improve their plasmonic lifetime based on the results of this study.